2021
DOI: 10.1101/2021.08.14.456361
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Angiotensin antagonist inhibits preferential negative memory encoding via decreasing hippocampus activation and its coupling with amygdala

Abstract: Exaggerated arousal and dysregulated emotion-memory interactions are key pathological dysregulations that accompany the development of post-traumatic stress disorder (PTSD). Current treatments for PTSD are of moderate efficacy and preventing the dysregulations already during exposure to threatening events may attenuate the development of PTSD-symptomatology. The present proof-of-concept study examined the potential of a single dose of the angiotensin II type 1 receptor (AT1R) antagonist losartan (LT) to attenu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…Consistent with the pharmacodynamics profile of LT (LT crosses the blood brain barrier and reaches peak plasma levels after 90 minutes and eliminates between 1.5-2.5h (24–27)), treatment was administered 90min before fMRI acquisition. Participants first performed a reinforcement learning task (duration 30min) followed by an emotional memory task (reported in Xu et al, 2021). To control for nonspecific effects of LT, assessments of mood, attention and memory were incorporated at baseline and after the experiment, while cardiovascular activity (i.e., blood pressure, heart rate) was measured at baseline, after drug administration and after the experiment (see Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the pharmacodynamics profile of LT (LT crosses the blood brain barrier and reaches peak plasma levels after 90 minutes and eliminates between 1.5-2.5h (24–27)), treatment was administered 90min before fMRI acquisition. Participants first performed a reinforcement learning task (duration 30min) followed by an emotional memory task (reported in Xu et al, 2021). To control for nonspecific effects of LT, assessments of mood, attention and memory were incorporated at baseline and after the experiment, while cardiovascular activity (i.e., blood pressure, heart rate) was measured at baseline, after drug administration and after the experiment (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Preclinical work in rodents and humans has utilized the selective competitive angiotensin II type 1 receptor (AT1R) antagonist losartan (LT) - an approved treatment for hypertension with an excellent safety record (10, 11) - to modulate learning from negative or positive events (12, 13). Recent human studies have demonstrated that a single dose of LT selectively suppressed memory encoding of threatening materials (14) and accelerated threat extinction learning (15, 16). Moreover, LT specifically affected probabilistic learning from negative outcomes by reducing the degree to which participants learned from loss feedback, while leaving learning from positive outcomes unaffected (12).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to activation analysis, and in the context of previous studies demonstrating the important role of amygdala-prefrontal circuits in anxiety and early fear detection processes (e.g. Becker et al, 2012; Janak & Tye, 2015; Mihov et al, 2013) as well as in mediating some fear and negative information processing related effects of LT (Reinecke et al, 2018; Xu et al, 2021; Zhao et al, 2019) we next examined effects of treatment on amygdala functional connectivity during fear vigilance. To this end, we employed a task-based functional connectivity analysis (generalized form of context-dependent psychophysiological interactions; gPPI (McLaren, Ries, Xu, & Johnson, 2012)) with identical first-level contrasts as the activation analyses and the bilateral amygdala from the Harvard-Oxford cortical and subcortical structural atlas (thresholded at 25% probability) as the seed region.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical studies have identified an important role of the angiotensin II system in stress- and anxiety-related disorders (Morrison & Ressler, 2014) and population-based studies suggest that pharmacological blockade of the angiotensin II type 1 receptor (ATR1) during trauma exposure decreases the incidence of subsequent post-traumatic fear symptoms (Seligowski et al, 2021). Experimental studies utilized the selective competitive ATR1 antagonist Losartan to demonstrate that ATR1 blockade facilitates fear extinction in rodents (Marvar et al, 2014) with subsequent pharmaco-fMRI studies in humans demonstrating that losartan has the potential to modulate threat-related amygdala functioning and circuits, including amygdala reactivity to threatening stimuli (Reinecke et al, 2018), amygdala-prefrontal connectivity during fear extinction (Zhou et al, 2019) and amygdala-hippocampal connectivity during fear memory formation (Xu et al, 2021). However, despite the important role of the extinction paradigm to map fear processing in translational models and despite the important role of the amygdala in fear processing (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation